Improving the Allocative Efficiency of the HIV Response Across the Care Cascade in Zimbabwe : Findings from a Modelling Analysis - Taramusi, Isaac; Sisimayi, Chenjerai; Benedikt, Clemens; Cheikh, Nejma; Fraser, Nicole; Shubber, Zara; Quiroga, Maria del Mar; Minnery, Mark; Martin-Hughes, Rowan; Kelly, Sherrie (World Bank, Washington, DC, 2020)
The report summarizes the findings of an allocative and implementation efficiency analysis of Zimbabwe's HIV response across the care cascade, which was conducted using the Optima-HIV model. The analysis was conducted to support Zimbabwe in its decision-making on strategic HIV investments, highlighting opportunities to maximise the impact of HIV financial resources in Zimbabwe through allocative and implementation efficiency gains.